Strategi Pengembangan Desa Wisata - Titing Kartika; Arisman Muchtar (Politeknik Baubau, 2023)
Ciburial Village is one of the Tourism Villages that has been established by the West Java Bandung Regency Government in accordance with the Bandung Regent's Decree Number 556.42/ Kep. 71- Dispopar/ 2011 Regarding the Determination of Tourism Villages in the Bandung Regency Area with the concept of Agriecotourism. In implementing the development of Tourism Villages, Ciburial Village encountered obstacles both in terms of human resources, destination management, marketing, and other aspects. The purpose of this study is to determine the development strategy of the tourism village. This study used a qualitative descriptive approach and SWOT (Strength, Weakness, Opportunity, and Threat) as an analytical tool. The results of the analysis of internal and external factors are processed using a SWOT matrix to produce several strategies. The results of the study indicate that strategies that need to be developed include mapping tourism based on potential, strengthening digital-based promotions as well as building branding, optimizing cross-sectoral coordination in the management of Tourism Villages and training in human resources including destination management and tour guides.